2002
DOI: 10.1016/s0014-5793(02)03063-6
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin content conditions insertion of daunorubicin within phosphatidylcholine monolayers

Abstract: Cell death induced by the chemotherapeutic drug daunorubicin (DNR) implicates an apoptotic pathway originating at the plasma membrane and characterized by sphingomyelin (SM) hydrolysis and ceramide generation. The mechanisms by which such a drug (hypothetically passively di¡using across a structural membrane) can trigger SM hydrolysis is unknown, but raises the question of the precise interaction between DNR and membrane lipid constituents. In this initial study, using alternative current polarography together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Since C is the second derivative of the surface tension respective to the potential [15], it follows that C is highly sensitive to minute variations of the surface pressure. This makes the method a valuable tool for the approach of PL layers interactions with various hydrosoluble molecules [16,17]. The differential capacity–potential curves (denoted C vs. E curve) were recorded at the interfacial equilibrium for all components.…”
Section: Methodsmentioning
confidence: 99%
“…Since C is the second derivative of the surface tension respective to the potential [15], it follows that C is highly sensitive to minute variations of the surface pressure. This makes the method a valuable tool for the approach of PL layers interactions with various hydrosoluble molecules [16,17]. The differential capacity–potential curves (denoted C vs. E curve) were recorded at the interfacial equilibrium for all components.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, hydrophobic interactions, membrane fluidity and drug lipophilicity are decisive for efficient drug import (Jedrzejczak et al, 1999;Schuldes et al, 2001). In line with these observations, it is of interest that the lipid composition of model membranes determines the efficiency of anthracycline translocation, and it is well conceivable that this also holds for natural membranes (Speelmans et al, 1994;Lecompte et al, 2002).…”
mentioning
confidence: 89%
“…Adsorption, insertion and flip-flop can be distinguished as consecutive stages in the transport of this compound across membranes (Regev and Eytan, 1997;Lecompte et al, 2002). Studies performed with model systems, such as large unilamellar vesicles, E. coli mutants and erythrocytes, revealed that membrane potential, pH and electrostatic forces play important roles in this (Terasaki et al, 1984;Nishiyama et al, 1992;de Wolf et al, 1993;Speelmans et al, 1997).…”
mentioning
confidence: 99%
“…We performed these studies on suitable model lipid monolayers with alternative current (AC) voltammetry, used under conditions allowing measurement of the electrical capacitance of a condensed lipid monolayer membrane constituting the interface between an electrolytic medium and a mercury electrode, and submitted to a variable applied potential. , Since this interfacial capacitance of the monolayer mainly depends on the nature and the arrangement of its constituting molecules, this approach has been previously successfully applied to gain information about the effects of various lipid compositions on the interfacial properties of a stable monolayer, , as well as for monitoring interactions of such a monolayer with exogenous small molecules , or with amphipatic proteins ,, added to the bulk aqueous electrolytic medium. Indeed, both interfacial capacitance and surface plasmon resonance studies have shown a two-step interaction of apolipoprotein A-I with monolayer membranes as a process relevant for initial HDL formation.…”
Section: Introductionmentioning
confidence: 99%